Adolescent perceptions of bystanders' responses to cyberbullying. (March 2017) - Patterson, Lisa J; Allan, Alfred; Cross, Donna
Cyberbullying can be harmful to adolescents using online technology, and one way of combating it may be to use interventions that have been successfully utilised for traditional bullying, such as encouraging peer bystander intervention. The online environment, however, differs notably from the environment in which traditional bullying takes place raising questions about the suitability of transferring traditional bullying approaches to the cyber environment. This study explored the perceptions of, and key influences on, adolescent bystanders who witness cyberbullying. In all, 24 interviews were conducted with students aged 13–16 years. Relationships emerged as a key theme with participants believing that a bystander's relationship with both the perpetrator and the target influenced whether they would intervene when witnessing cyberbullying. Relationships also influenced their ability to understand the context of the situation, the perceived severity of the effect of the incident on the target and therefore the need, or otherwise, to seek help from adults.